EFL child peer interaction: Measuring the effect of time, proficiency pairing and language of interaction - Pladevall-Ballester, Elisabet; Vraciu, Alexandra (Studies in Second Language Learning and Teaching, 2020)
Child peer interaction in English as a foreign language (EFL) settings has recently received increasing attention with respect to age, instruction type and first language (L1) use, but longitudinal studies remain scarce and the effects of proficiency pairing and language choice on meaning negotiation strategies are still rather unexplored. Within a primary school EFL context, this paper aims to explore the amount and types of meaning negotiation, and the effects of time, proficiency pairing and language choice in a spot-the-differences task. Forty Catalan/Spanish bilingual children were paired into mixed and matched proficiency dyads, and their oral production was analyzed twice over the course of two years (i.e., 9-10 and 11-12 years old). The analysis included conversational adjustments, self- and other-repetition and positive and negative feedback in the learners’ L1 and second language (L2). Our data show that the amount of meaning negotiation is low, although L2 meaning negotiation is higher than L1 meaning negotiation, and all the strategies are present in the data except for comprehension checks. Time effects are hardly observed. However, proficiency pairing and language effects are more generally found, whereby mixed proficiency dyads tend to negotiate for meaning more than matched dyads and meaning negotiation instances are more frequent in the L2 than in the L1.